Use of water from air conditioning using arduino and photovoltaic panels for automatic irrigation of vegetables - Jesus, Adriano Freitas de; Marco, Marcus Vinícius Martins; Rios, Pedro Lopes; Luz, Albert Meneses Gonçalves; Pereira, Luan Diego de Lima (Brazilian Journal of Production Engineering, 2024)
This paper explores the implementation of the irrigation system using water from air conditioning systems at the Instituto Federal da Bahia (IFBA), Campus Feira de Santana, analyzing the technical feasibility and environmental benefits of this initiative. The system operates with water from the air conditioning drain, stored in a plastic bottle. Using Arduino, water pump and humidity sensors, automated irrigation control is carried out. The system not only brings efficiency in the management of water resources and renewable energy, but also stands out as a sustainable model for educational institutions, promoting the reuse of air conditioning water and inspiring ecologically responsible practices.